Current Developments Under the Robinson-Patman Act - Joseph E. Sheehy (Washington University Law Quarterly, 1960)
Text of remarks presented by Mr. Sheehy to the Round Table on Trade Regulation at the 1959 annual meeting of the Association of American Law Schools, held at St. Louis, Missouri, December 29, 1959: The matter of area price discrimination is one which is receiving increasing attention and one on which there is relatively little case law. This despite the fact it unquestionably was one of the major targets of Congress at the time of the passage of both the original Clayton Act and the Robinson-Patman Amendment. This practice of lowering prices in one geographic area while maintaining or enhancing them elsewhere enables large companies with interstate treasuries to subsidize local price cutting without material impairment of their over-all profits.
Keywords: Prices